Operationalization of functions definitions: a trigger process of meaningful learning of the concept of function - Santos de Souza, Jerson Sandro (2019)
In this paper, we discuss the importance of defining the concept of function for meaningful learning. The articulation of the multiple representations of this concept allows its apprehension, so to favor the articulation becomes fundamental. It is believed that, in order to achieve articulation, definitions are indispensable, since they provide forms of reasoning that make them useful as connecting elements of other representations. We are not referring to the simple act of enunciating a definition, but rather to the process in which the learner consciously uses it to interpret situations based on functional relations, a process we call the operationalization of function definition. Thus, this research is guided by the following research question: How could the operationalization of the function definition, admitted as a didactic-methodological element, favor the meaningful learning of the concept of function? To verify the hypothesis that the operation facilitates the articulation, and this, in turn, enables meaningful learning, we apply three didactic sequences, based on aspects favoring the operationalization. Twenty secondary students from a public school in the city of Manaus-AM were involved. The results, from the confrontation between a priori and a posteriori analyzes, that is one of the phases of didactic engineering, which was the adopted research methodology, suggest benefits to learning, which are due to the evolution of the use of a definition: from an inert definition, abandoned from any reasoning immediately after stated, to an operational definition, used as a guiding source of functional thinking. We conclude that an operational definition could be seen as a triggering element of the process of meaningful learning of the concept of function.